2011
DOI: 10.1016/j.chroma.2011.07.039
|View full text |Cite
|
Sign up to set email alerts
|

iMatch: A retention index tool for analysis of gas chromatography–mass spectrometry data

Abstract: A method was developed to employ National Institute of Standards and Technology (NIST) 2008 retention index database information for molecular retention matching via constructing a set of empirical distribution functions (DFs) of the absolute retention index deviation to its mean value. The effects of different experimental parameters on the molecules’ retention indices were first assessed. The results show that the column class, the column type, and the data type have significant effects on the retention inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…For metabolite identification using ChromaTOF, each chromatographic peak was tentatively assigned to a metabolite if its experimental mass spectrum and a database spectrum have a spectral similarity score no less than 600. The retention index matching in MetPP was performed using the iMatch method with the P value threshold set as P # 0.001 (Zhang et al, 2011). The pairwise two-tail t test was used to determine whether a metabolite had a statistically significant abundance difference between sample groups by setting the threshold of false discovery rate q # 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…For metabolite identification using ChromaTOF, each chromatographic peak was tentatively assigned to a metabolite if its experimental mass spectrum and a database spectrum have a spectral similarity score no less than 600. The retention index matching in MetPP was performed using the iMatch method with the P value threshold set as P # 0.001 (Zhang et al, 2011). The pairwise two-tail t test was used to determine whether a metabolite had a statistically significant abundance difference between sample groups by setting the threshold of false discovery rate q # 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures for determination of RI search windows (RI thresholds) were considered in several articles [43][44][45][46]. Barnes et al [47] suggested a methodology called "retention projection", which can overcome the limitations of shared chromatographic databases, such as a relatively large spread of retention data in different databases.…”
Section: Retention-index Data Distributions and Search Windowsmentioning
confidence: 99%
“…Currently, MetPP can perform retention index matching only for the first dimensional GC. We improved the algorithms of iMatch approach (Zhang et al, 2011) by enabling retention index matching of multiple top-ranked identification results, to ensure that the true metabolite can still be preserved even though it may not have the best score for mass spectral matching (Koo et al, 2011). We further updated the retention index database used in iMatch to NIST11 retention index database and calculated all retention index distributions.…”
Section: Retention Index Matchingmentioning
confidence: 99%